Use of Lactobacillus plantarum (strains 22F and 25F) and Pediococcus acidilactici (strain 72N) as replacements for antibiotic-growth promotants in pigs - Pawiya Pupa (Nature Portfolio, 2021)
Abstract The lactic acid bacteria (LAB) Lactobacillus plantarum (strains 22F and 25F) and Pediococcus acidilactici (strain 72N) have appeared promising as replacements for antibiotics in in vitro﻿ studies. Microencapsulation, especially by the spray-drying method, has been used to preserve their numbers and characteristics during storage and digestion. This study compared the efficacy of these strains and their microencapsulated form with antibiotic usage on growth performance, faecal microbial counts, and intestinal morphology in nursing-finishing pigs. A total of 240 healthy neonatal pigs were treated on days 0, 3, 6, 9, and 12 after cross-fostering. Sterile peptone water was delivered orally to the control and antibiotic groups. Spray-dried Lactobacillus plantarum strain 22F stored for 6-months was administered to piglets in the spraydry group. Three ml of each the three fresh strains (109 CFU/mL) were orally administered to piglets in each group. All pigs received the basal diets, but these were supplemented with routine antibiotic for the antibiotic group. Pigs in all the probiotic supplemented groups exhibited a better average daily gain and feed conversion ratio than those of the controls in the nursery and grower phases. Probiotic supplementation increased viable lactobacilli and decreased enterobacterial counts. Antibiotic additives reduced both enterobacterial and lactobacilli counts. Villous height and villous height:crypt depth ratio were greater in probiotic and antibiotic supplemented pigs comparing to the controls, especially in the jejunum. The results demonstrated the feasibility of using these strains as a substitute for antibiotics and the practicality of the microencapsulation protocol for use in swine farms.